(untitled) (Research, Society and Development, 2022)
The article aims to propose the implementation of the lean healthcare methodology for a health center along with the development of an application that helps in this process. For this, the article makes an approach to the Lean methodology focused on the healthcare area where it seeks to emphasize the quality management, reducing costs and waste for the public management, thus benefiting the population and employees at the same time. It was used the method of literature review about the theme, along with semi-structured interviews in a remote way, because it was still with high rates of infection of the virus corona, with the managers of the center to have information about the operation and methodologies applied, using later the NVIVO 11® software for analysis of the interviews. Where it is perceived that even following the guidelines of the municipality and ministries the system needs tools focused on quality management, thus arising the proposal of the methodology under study. As final considerations it became evident that there is a need to work an organization focused on quality management, where the proposed application would assist in the implementation of the process.